Myocyte necrosis is the basis for fibrosis inrenovascular hypertensive rats - Okoshi, M.P.; Matsubara, L.S.; Franco, M. [UNESP]; Cicogna, A.C.; Matsubara, B.B. (Associação Brasileira de Divulgação Científica (ABRADIC), 1997)
The pathogenesis of fibrosis and the functional features of pressure overload myocardial hypertrophy are still controversial. The objectives of the present study were to evaluate the function and morphology of the hypertrophied myocardium in renovascular hypertensive (RHT) rats. Male Wistar rats were sacrificed at week 4 (RHT4) and 8 (RHT8) after unilateral renal ischemia (Goldblatt II hypertension model). Normotensive rats were used as controls. Myocardial function was analyzed in isolated papillary muscle preparations, morphological features were defined by light microscopy, and myocardial hydroxyproline concentration (HOP) was determined by spectrophotometry. Renal artery clipping resulted in elevated systolic arterial pressure (RHT4: 178 ± 19 mmHg and RHT8: 194 ± 24 mmHg, P<0.05 vs control: 123 ± 7 mmHg). Myocardial hypertrophy was observed in both renovascular hypertensive groups. The myocardial HOP concentration was increased in the RHT8 group (control: 2.93 ± 0.38 µg/mg; RHT4: 3.02 ± 0.40 µg/mg; RHT8: 3.44 ± 0.45 µg/mg of dry tissue, P<0.05 vs control and RHT4 groups). The morphological study demonstrated myocyte necrosis, vascular damage and cellular inflammatory response throughout the experimental period. The increased cellularity was more intense in the adventitia of the arterioles. As a consequence of myocyte necrosis, there was an early, local, conjunctive stroma collapse with disarray and thickening of the argyrophilic interstitial fibers, followed by scarring. The functional data showed an increased passive myocardial stiffness in the RHT4 group. We conclude that renovascular hypertension induces myocyte and arteriole necrosis. Reparative fibrosis occurred as a consequence of the inflammatory response to necrosis. The mechanical behavior of the isolated papillary muscle was normal, except for an early increased myocardial passive stiffness
Keywords: coronary vascular remodeling; myocardial function; pressure overload hypertrophy; papillary muscle; reparative fib